Longitudinal muscular column in the prostatic urethral wall: Its form, shape, and possible function based on mathematical simulation in ejaculation. Issue 6 (12th February 2020) - Hur, Mi‐Sun; Lee, Hye Won; Yang, Hun‐Mu; Kwon, Hyun‐Jin; O, Jehoon; Lee, Seunggyu; Oh, Chang‐Seok
Abstract: Background: The shape and function of the longitudinal muscular column (LMC) of the prostate have not been established in detail. The present study was undertaken to elucidate the roles of the LMC of the posterior wall of the prostatic urethra (PSU) in the emission phase of ejaculation by investigating the form and muscular arrangement of the LMC. Methods: Prostates and urinary bladders were obtained from 14 Korean adult cadavers. Nine specimens were histologically analyzed using hematoxylin and eosin, Masson's trichrome, and Verhoeff‐van Gieson staining. Two specimens were scanned using microcomputed tomography (micro‐CT), and all scanned images were reconstructed into a three‐dimensional model. Results: At the proximal level of the prostate, the ejaculatory ducts (EDs) and prostatic utricle (PU) together were surrounded by circular smooth‐muscle fibers. However, at the seminal colliculus (SC) where the EDs and PU opened, they were mainly surrounded by an abundance of longitudinal fibers. The longitudinal fibers posterior to the EDs and PU formed a distinctive LMC in the posterior urethral wall. In histologic sections and micro‐CT images, the LMC extended distally from the level of the SC to the level of the membranous urethra (MBU). We simulated a potential mechanism of LMC using a mathematical model of its movements. Conclusions: Comprehensive analyses based on in‐depth assessment of histologic characteristics and micro‐CT images demonstrated extension of the LMC from the level of the SC to the level of the MBU, enabling a better understanding of ejaculation physiology involving the LMC. These results suggest that the LMC in the posterior wall of the PSU is a critical component of ejaculation by facilitating the ejection of seminal vesicle fluid into the PSU via well‐coordinated contractions.